2007
DOI: 10.1111/j.1471-6712.2007.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

A life enriching togetherness – meanings of informal support when being a parent of a child with disability

Abstract: The majority of children affected by disability are cared for at home by their parents. It is well documented in research literature that the parents are in need of professional support. In the striving to improve the professional caring, it is also important to deepen our understanding about the meaning of informal support from the perspective of parents' life world. The aim of this study was to illuminate the meanings of lived experience of informal support, when being a parent of a child affected by disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…Informal supportive sources (family circle, caregiver, etc.) enrich the life (Lindblad, Rasmussen, & Sandman, ), render the parents to feel better (Raina et al., ), and to feel less tired (Giallo, Wood, Jellett, & Porter, ). The most prominent factor that affects the parents' stress is the load of the child's care (Van Riper, ).…”
Section: Discussionmentioning
confidence: 99%
“…Informal supportive sources (family circle, caregiver, etc.) enrich the life (Lindblad, Rasmussen, & Sandman, ), render the parents to feel better (Raina et al., ), and to feel less tired (Giallo, Wood, Jellett, & Porter, ). The most prominent factor that affects the parents' stress is the load of the child's care (Van Riper, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the impact of the children's congenital anomaly on mothers' social relationships may have an extra and possibly positive implication. A recent Swedish study on informal support to parents of a disabled child showed that friendship was tested: Only those persons who respected parents' obligations to their children's care were considered friends (Lindblad, Holritz-Rasmussen, & Sandman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such supporters typically include family members, with parents providing the bulk of the support, followed by adult siblings and, to a lesser extent, family friends, acquaintances and neighbours (Prosser & Moss ; Lindblad et al . ; Duggan & Linehan ; Sanderson et al . ).…”
mentioning
confidence: 99%
“…In addition to formal supports, many adults with IDDs rely on informal, or natural, supports to meet their daily needs. Defined as voluntary and unpaid assistance, informal supports are often provided by family members, friends, neighbours and other community members (Lindblad et al 2007;Duggan & Linehan 2013). Such informal help contrasts with help from teachers, case managers, group home workers or other paid professionalspeople whose job is to assist the individual with disabilities (Clement & Bigby 2009;Milner & Kelly 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation